Mapalus as a Socio-Cultural System in Minahasa Society - Yoseph Daniel Arie Santie,; Aldegonda. E Pelealu,; Syafrida Selfiardy,; Susi Aryani Manangin4,; Habibi Sultan, (Technium Education and Humanities, 2024)
This study aims to examine Mapalus as a socio-cultural system in Minahasa society, with a focus on an in-depth understanding of its historical roots, core values, roles in social structures, and adaptations and challenges faced in the modern era. The method used is a qualitative approach with a literature review type of research, involving a comprehensive analysis of various literature sources including books, journal articles, historical documents, and publications related to Mapalus and Minahasa culture. The results of the study indicate that Mapalus is a mutual cooperation system that has been deeply rooted in Minahasa society since ancient times, reflecting the values of cooperation, solidarity, and reciprocity. Mapalus has been shown to have an important role in the formation of social cohesion, resource management, and local economic development. Despite facing the challenges of modernization, Mapalus shows adaptability, evolution of form, and potential as a development model based on local wisdom. This study concludes that Mapalus remains relevant and has the potential to be a source of inspiration for the development of sustainable community-based development models.